Can a feedback report and training session on medication counseling for general practitioners improve patient satisfaction with information on medicines? - Mahler, Cornelia; Krug, Katja; Jank, Susanne; Haefeli, Walter E.; Szecsenyi, Joachim (Patient preference and adherence, 2012)
Background Regular intake of medicines prevents hospitalization and improves treatment outcomes in patients with chronic diseases; however, requires good patient-physician communication. Yet, this communication is often insufficient and characterized by misunderstandings. This paper aimed to explore whether a training session on medication counseling for general practitioners (GPs) can improve patient satisfaction about information on medicines. Methods Within a seamless care project (HeiCare®), a questionnaire to assess patient satisfaction with information on medicines and other questions related to medication issues was distributed among 370 patients. Results were returned to physicians in a feedback report, discussed in a training session, and a subsequent second questionnaire was sent to patients. Results Patients showed a significant increase in satisfaction with overall information on medicines and with information on potential problems when experiencing medication counseling after their GP received a feedback report and/or training session. Conclusion Individual feedback and training sessions can improve medication counseling and GPs’ awareness of patients’ attitudes toward medicines and thus increase patients’ satisfaction with medicines information received. Regular feedback to the GP on patients’ satisfaction with information and patients’ beliefs in medicines can be obtained by patient surveys or by addressing these issues in regular medication counseling encounters. Physicians need to be trained to listen to patients’ views and concerns on medication.